Structural Characterization And Reactivity Studies Of Several Triruthenium Carbonyl Cluster Complexes Mediated Via P–C/As–C Bond Cleavage And C–H Bond Activation - Sirat, Siti Syaida (2018)
The development of metal carbonyl cluster mediated Group 15 ligand transformations continues to be an area of active research. It is therefore of considerable interest to investigate the thermolysis reactions of triruthenium carbonyl cluster complexes containing diphosphines with long chain carbon backbone [1,3-bis(diphenylphosphino)propane (dppp) and 1,4-bis(diphenylphosphino)butane (dppb)]; anticipating that the introduction of more than one methylene carbon backbone of diphosphine ligands would radically alter its reactivity leading to new reaction products. Series of Ru3(CO)10(L-L), [Ru3(CO)11]2(L-L) [where L-L = 1,3-bis(diphenylphosphino)propane (dppp), 1,4-bis(diphenylphosphino)butane (dppb), 1,5-bis(diphenylphosphino)pentane (dpppe) and 1,6-bis(diphenylphosphino)hexane (dpph)], Ru3(CO)8(L-L)] [ where L-L = 1,1-bis(diphenylarsino)methane (dpam)] and Ru3(CO)9(μ-dppb)(L') [where L' = PPh3 and AsPh3] were prepared by substitution reactions initiated by Na[Ph2CO] and thermal method. The variation of Ru-Ru bond lengths in Ru3(CO)10(L-L) were found to be related with intracyclic metal-metal-ligand [Ru–Ru–P] angles. Twenty-eight complexes have been prepared and characterized by spectroscopic and analytical techniques. Twenty-one of these have been structurally characterized by using single crystal X-ray crystallography.